Analisando a eficiência alocativa dos royalties do petróleo: o caso dos municípios fluminenses - Adelino, Viviane Mirela (Universidade Federal Rural do Semi-Árido, 2018)
This study had as main objective to analyze the efficiency of the allocation of resources of the oil and natural gas royalties, specifically, the allocative efficiency of these resources was investigated in the municipalities of the State of Rio de Janeiro. For this purpose, data from the Firjan Index of Municipal Development, oil and natural gas royalties and per capita revenues associated with the Data Envelopment Analysis (DEA) methodology were used. The main results show an average inefficiency of 34% in the management of public resources for education, health and infrastructure. In addition, the results pointed out that municipalities that receive large amounts of resources of this nature, such as Macaé and Campos dos Goytacazes, are among the worst in the analysis. Respectively, the findings report an inefficiency around 67% and 78% for these municipalities. In addition, when comparing the development of the municipalities of Rio de Janeiro with other Brazilian municipalities not covered by these resources, development is well below that. These factors allow us to suspect that the economic phenomenon "the curse of natural resources" may be occurring in the municipal economies of Rio de Janeiro.
Monografia
Keywords: Royalties do petróleo e gás; Oil and gas royalties; Análise envoltória de dados; DEA; Recursos públicos; Public resources; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA